Knowledge and Media Workers in the Global Economy: Antimonies of Outsourcing. - Mosco, Vincent (Social Identities, 2006)
The outsourcing of jobs, particularly the growing practice of sending the jobs of US knowledge and communication sector workers to other countries, has become a significant issue in academic, policy and media circles. This paper draws from a research project that examines labour, its unions and social movements in the knowledge and media sectors to describe what we know about outsourcing and assess its significance for media scholars. The paper begins by defining the knowledge worker category and by assessing debates about its significance which date from the 1950s. It next considers major views about the problems which centre on the fear of massive job loss to low-wage nations, especially India and China, and addresses solutions offered by organized labour which call for stopping outsourcing wherever possible, and by business which maintains that outsourcing can only be curtailed when business and labour grow smarter. Each of these views conveys an essential truth but each deals only with symptoms of a significant transformation in the international division of labour. Understanding this transformation, and the role of information and communication technologies, leads us to consider key dimensions in the complexity of outsourcing, Specifically, developed nations like Canada, especially in film and video, and Ireland, in new media and IT, have benefited as recipients of outsourced jobs. Less developed nations like India are not just recipients of outsourced jobs, they are beginning to lead the process. In spite of ‘end of geography’ promises, place matters and culture counts. Finally, resistance takes a multiplicity of forms, including new forms of old unions and new types of worker movements in the knowledge and media sectors. The paper concludes that we need to go beyond the generally accepted views that outsourcing is about sending jobs to low wage countries and that it can be stopped, or at least limited, either by regulation or by developing new and smarter business practices. It signals a fundamental transformation in the international division of labour that is accelerating especially in the knowledge and media sectors. Media scholars need to pay closer attention to these significant changes in the global production process.